Growth, FDI, Imports, and their Impact on Carbon Dioxide Emissions in GCC Countries: An Empirical Study - Kari, Fatimah; Saddam, Ahmed (Mediterranean Journal of Social Sciences, 2012)
The Gulf Cooperation Council countries are among the top 25 countries in terms of their contribution to increasing the level ofcarbon dioxide emissions more than the average world. Furthermore, these countries emit from 45% to 50% of the total emissions ofArab countries, because of the significant role of extractive sectors, as major sources of income in these economies. This studyexamines the most important factors pertaining to the increasing carbon dioxide emissions in GCC countries over the period 1998-2008.In this paper, the research objective is to determine how much the FDI inflows, economic growth, and commodity imports influenced theincreasing level of emissions during the period of study, and which variable has most effect? For this purpose, an empirical model will beestimated in order to obtain the impact of the said variables of the six member countries – United Arab Emirates, Bahrain, Saudi Arabia,Oman, Qatar, and Kuwait. The model of carbon dioxide emissions as a function of FDI inflows, per capita GDP growth rate, andcommodity imports will be examined simultaneously within the panel data technique using ordinary least squares OLS.